THE IMPACT OF CAMPUS COUNSELING SERVICES ON STUDENT ACADEMIC FUNCTIONING - Priniski, Stacy J. (My University, 2013)
This study examines the impact of counseling services received at a university counseling center on academic functioning. Previous research has found conflicting results that appear to vary by the type of outcome measure used, with differences found between self-report and objective measures of academic functioning. To clarify those conflicting results, changes in academic functioning over time using both self-report and objective measures were examined. Across two studies, the impact of counseling was measured within a sample of counseling clients and using a matched control group of non-clients of the counseling center. Client-participants completed self-report measures of academic functioning at their intake (first) and fifth appointments, and grade point average (GPA) of the prior and current semester were collected. Changes in academic functioning and GPA over time were examined. First-year clients were then matched to a non-client control group. Clients' and non-clients' academic adjustment at the beginning of the term and first-semester college GPA were compared. Generally, it was hypothesized that counseling would have a positive impact on academics, and that the degree of improvement would depend on levels of academic functioning before counseling and levels of improvement in psychological functioning over the course of one semester in counseling. The results of the current studies replicated the mixed results of previous research within each sample. The extent to which counseling was found to impact academics differed based on which measure was used. Implications for research on counseling and academics are discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Psychology - Cognitive and Affective Science
Keywords: College students - attitudes; College dropouts; College students - mental health services; Counseling in higher education